THE RELEVANCE OF TOLERANCE AND FORGIVENESS TO THE MAINTENANCE OF PEACE AND DEVELOPMENT OF A NATION: AN ISLAMIC EDUCATION PERSPECTIVE - Jimoh, Muhammad Usman (Sokoto Educational Review, 2020)
In a bid to make life meaningful, beautiful and fruitful for man, Islamic education avails man with all he needs in all spheres of life so as to achieve the said goals. With all the provisions contained in the Glorious Qur’an, the prophetic traditions and various explanations of Islamic scholars coupled with all other sources from which this field derived its source, one is rest assured that each and every aspect of its teachings is worthwhile for man to know in life. A very good example is its teachings on tolerance and forgiveness which this paper viewed as being worthy of mentioning in relation to peace and development o f a nation. The paper assessed tolerance and forgiveness as inevitable in man’s life and considered the consequences of lack of adoption of tolerance and forgiveness in man to man relation and in his relationship with his Lord. Furthermore, the paper discussed some ways by which this could be achieved from the Islamic Education perspectives.